(untitled) (Journal of the College of Education for Women, 2019)
As we have said that the reasons for abortion are many and varied them to be forthe purpose of treatment or the protection of the mother of the loss or that the abortionof an act intended purpose of birth control or other reasons is the statistics that arespread in the world that about 50-60 million abortions annually in the world If thisabortion criminal who is loss of the lives of fetuses and a disgrace to the preachers tothe progressive and liberal, secular, and because they were not able to maintainhuman life after leaving the obligation to approach Islam and because life support isthe highest things, which is one of the necessities of the five obligatory streetmaintenance came verses warn those who underestimate the death of the verse: (Andwhoever kills a believer intentionally, his recompense is Hell to abide therein and thewrath of God upon him, and prepared for him a great punishment) Women: 93.Therefore, it has been reached to the most important objectives of the researchare:First: the whole jurists on the sanctity of abortion after the soul is breathed into thefetus Wang is killed for the same as abortion after the soul is breathed into the loss ofspirit and the destruction of the body is killed for the same as the loss of the spirit ofkilling is achieved up taking the soul, and spirit have been resolved the body after thefourth month The attack by the loss of those Spirit embryo after entering the stage ofthe soul is breathed is permissible to describe humans and worthy of respect, whichbestowed on the son of Adam on the right of life, and an estimated four months afterpregnancy on the basis of the Hadith from Ibn Masood may Allah be pleased withhim narrated that the Messenger of Allah peace be upon him, a sincere andtrustworthy: ( that combines one of you created in the womb for forty days, then thesperm will be such a leech and then the embryo such as that and then breathed intohim).Second: we say that the origin of abortion is a risk, but some scholars say it ispermissible to abort a pregnancy before the soul has been breathed before four monthsof pregnancy for a reason acceptable to drop Kalmarbp chronic illness or Kalmrdap ifhit by the rope and cut off the milk and not to Abu small pregnancy what rent by Zirany nursing and afraid of loss of the child and clear from this that abortion before thelapse of four months of pregnancy to the imperatives of miscarriage treatment is alegitimate reason.Third: If the breed of the human community which is urged by the Holy Prophetpeace be upon him said: (I am married loving and fertile Propagated you prophets, theDay of Resurrection). Abortion is to minimize the illiterate and weakening of the veryleast, the incidence of abortion up to about 50-60 million abortions a year and morethan half of these cases occur in developing countries is it possible to say that it ispermissible abortion of millions of embryos and pieces of life for them to desire acasual or lust hidden.Fourth: the legal rules established to ward off evil takes precedence overbringing benefits has proven good that abortion was a major women’s health and hasinfluences serious organ towns where Dr. Frederick Tasc: that the pregnancy when it comes out before completion, there are three damage against birth control human forhim: A. Destroy an unknown number of human will to get out before the light of life.B. Go number fraction of maternal death during a victim of the abortion process.C. Occur in women effects satisfactory significant number.Fifth: that a pregnant woman if the limit does not deserved to be held only aftertake pregnancy The suspension is the extent that the rule of God in order to rule onthe inadmissibility of evidence to abort the pregnancy if it was permissible topermissible here a fortiori.And weighting that which seems to me is that it is not permissible to abortionand the sanctity of abort a pregnancy at any stage of Otourah because all of theembryo in which a decent life is the life of growth and numbers in contrast to thosewho they endorse before the soul is breathed into doing so, they open the doordifficult to close and put in the hands of enemies of Islam and its enemies a weaponstab tags Islam and justify it as being in non-Muslim country of scandals andantipathic shook the church and the clergy, so that we have already mentioned webelieve that the prevailing view is the view that the sanctity of the projection at allstages and that which went to most of the Maalikis and some Shafi’i and Hanafi andforward and shared their belief in God, I know.